Qualitative market segmentation of broiler grillers by using alternative proteins to soybeans and lipid sources in feeding programmes. Issue 2 (4th March 2021) - Baéza, E.; Lessire, M.; Chartrin, P.; Juin, H.; Méteau, K.; Guillevic, M.; Chesneau, G.
ABSTRACT: 1. The aim of the present study was to investigate increasing amount of n-3 fatty acids (FA) in common edible chicken meat cuts by testing different levels of extruded linseeds (LS) and rapeseed oil in growing and finishing diets. Another challenge was to replace a part of soybean meal by faba beans. 2. For that purpose, 3168, one-day-old Hubbard JV15 strain chickens were distributed into six groups: R1 = control diet, R2 = 3% then 5% LS, R3 = 4% then 6% LS, R4 = 5% then 7% LS, R5 = 3% then 5% LS and a low amount of soybean meal in the finishing diet and R6 = 3% then 5% LS and no soybean meal in the finishing diet. The growing performance was recorded throughout the trial. At 30 days of age, all chickens were slaughtered in a commercial slaughter plant at an average weight of 1322 g, to mirror the production of low body weight 'broiler griller' birds commonly available for export markets. Thirty carcases per group were processed to determine cut yields. The edible parts from each half carcase were removed to determine the chemical composition and fatty acid composition of meat with skin. The sensorial quality of thighs was evaluated for 20 carcases per group, after roasting. The environmental and economic impacts of the feeding programmes were further evaluated. 3. This study showed that it was possible to replace a part of the soybean meal in finishing diet by faba beans and to enrich meat with n-3 FA of broiler meat portions without altering growth performance, carcase composition and sensorial quality of meat. The environmental impact was reduced by these dietary interventions, whereby climate change parameters, expressed as kg CO2 eq./T, and phosphorus and fossil energy consumption were lower, but the land occupation was increased. The extra feed cost was +3 to +8% for groups fed R2 to R6 compared to the control group R1.